Strain rate effect on the mechanical properties of a glass fibre reinforced acrylic matrix laminate. An experimental approach. (1st September 2019) - Cadieu, L.; Kopp, J.B.; Jumel, J.; Bega, J.; Froustey, C.
Abstract: The aim of this study is to evaluate the effect of the loading rate on the mechanical properties and damage mechanisms of a Glass/Elium150 laminate composite. Quasi-static indentation (QS) and low energy dynamic impact (DYN) tests which simulate lifetime structural loadings (dropped tool, gravel impacts, …) are lead. A specific experimental approach is developed to compare results of both experiments. The effect of the loading rate on the structural response (stiffness, dissipated energy) of the composite is highlighted. The numerous damage mechanisms involved in the collapse of the material are observed at a microscopic scale using both optical and scanning electron microscopy (SEM). Finally an intra-laminar crack propagation mechanism is described based on post-mortem observations at ply scale to explain the formation of interlaminar cracks.